2018
DOI: 10.5296/jpag.v8i4.13894
|View full text |Cite
|
Sign up to set email alerts
|

Local Economic Development Strategies and Challenges: A Comparative Empirical Evidence from Ghana’s Local Governance System

Abstract: Local level economic development has eluded Ghana since independence. This was because most policies were centralized. As a result, focus was shifted to local economic development. This article comparatively examined the local economic development strategies implemented in three of Ghana’s Metropolitan, Municipal and District Assemblies. Using the mixed method and multiple case study approaches of research, the study sampled a total of 533 respondents across the three Metropolitan, Municipal and District Assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In addition, Akpeko (2018) found that bureaucracy in starting a business is a common problem in most of LGAs in Ghana. Similarly, Khumalo (2015) concluded that the governance system in South Africa is rather complex as various layers of the government intervene in private sector development at the local level.…”
Section: Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Akpeko (2018) found that bureaucracy in starting a business is a common problem in most of LGAs in Ghana. Similarly, Khumalo (2015) concluded that the governance system in South Africa is rather complex as various layers of the government intervene in private sector development at the local level.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Existing literature such as Akpeko (2018) has addressed challenges on the supply side only (i.e. the government's side) and very few studies in Africa such as Akudugu and Laube (2013) have identified LED challenges faced by the demand side (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local authorities have a role in promoting economic growth through local policies and practices that encourage and attract investments in the localities; they have to play an active role in guiding local resources to achieve local economic development (LED) objectives. Local authorities are considered catalysts for improved business promotion services in an environment of improved economic governance and investment in infrastructure (Agbevade, 2018;Akudugu, 2018;Hilhorst et al, 2008;Koma, 2012;Meyer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several challenges are also mentioned in reference to LED. These include limited legislative mandates and frequent changes in policies, inconsistency in policies, less positively impacting economic policies, low commitment to the empowerment of the LGA's, limited reach of LED pilot projects, low understanding of LED approaches and significance, limited efforts and appreciation of publicprivate partnerships benefits, low available resources and skills, dependence on national or external catalyst to adopt LED, short-term perspectives on LED, limited stakeholder involvement that is not mainstreamed into LGAs practices, absence of champions on LED, and so on (Sarpong et al, 2020;Agbevade, 2018;Akudugu, 2018;Meyer, 2014;UCLG, 2016).…”
Section: Introductionmentioning
confidence: 99%